Implementasi Building Information Modelling Menggunakan Software Infraworks Untuk Perencanaan Jalan: Studi Kasus Ruas Jalan Politeknik Negeri Lampung - Ranto Tumangger; Resti Agustina; Tanya Audia Balqis (Politeknik Negeri FakFak, 2024)
Road design is part of infrastructure development that supports an area or environment. In this context, the use of Building Information Modeling-based design technology such as Infraworks promises significant progress in the planning and design process of road infrastructure. This research aims to implement infraworks applications in road design through implementation case studies in the Polinela campus road design project.This research methodology includes field data collection, secondary data processing, making 3D road models. The research results show that the use of Infraworks significantly increases efficiency in the road design process by integrating various features such as topographic modeling, hydrological analysis, and integrated project visualization.The conclusion of this research shows that the use of Infraworks in road design has great potential to increase project efficiency, collaboration and sustainability. With a deep understanding of the benefits and challenges of using Infraworks, stakeholders can take steps to optimize the application of this technology in sustainable road infrastructure design practices